Impact of foreign direct investment and trade openness on economic growth of Bangladesh: an empirical analysis - Hossain, Proma (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Applied Economics, 2019.